Functional Implications of Flat-Topped Talus Following Treatment of Idiopathic Clubfoot Deformity. (April 2023) - Siebert, Matthew J.; Zide, Jacob R.; Shivers, Claire; Tulchin-Francis, Kirsten; Stevens, Wilshaw; Borchard, Justine; Riccio, Anthony I.
Background: Though flatness of the talar dome (TD) is a potential consequence of operative and nonoperative clubfoot management, the functional impact of this deformity is not well understood. This study analyzes the relationship between TD morphology and ankle function at skeletal maturity in patients treated for idiopathic clubfoot during infancy. Methods: 33 skeletally mature patients (average age 17.9 years) with 48 idiopathic clubfeet were identified. Weightbearing radiographs, gait analysis, and patient-reported outcomes using the Pediatric Orthopaedic Data Collection Instrument (PODCI) were obtained. Radius of curvature (ROC) of the TD and tibial plafond were measured along with other parameters of talar and calcaneal morphology. All measurements were correlated to PODCI scores and gait analysis data. Results: Patients demonstrated marked variability in ROC of the TD (mean 30.8 mm, SD 13.6 mm), TD radius to talar length (R/L) ratio (mean 0.56, SD 0.28), opening angle of the TD (alpha angle) (mean 89.6°, SD 28.4°), and tibiotalar incongruity index (mean 0.18, SD 0.16). Increased tibiotalar incongruity index correlated with decreased maximum plantar flexion ( r = ‒0.325, P = .02). A less acute alpha angle of the talar dome correlated with increased maximum ankle power generation ( r = 0.321, P = .03) as did increased length of the talar neck ( r = 0.358, P = .013). Increased tibiotalar incongruity index correlated negatively with PODCI global function domain scores ( r = ‒0.490, P = .04; r = ‒0.381, P = .03, respectively), whereas length of the talar body correlated with higher global function scores ( r = 0.376, P = .03) and lower pain scores ( r = 0.350, P = .046). Conclusion: At skeletal maturity, flattening of the talar dome and tibiotalar incongruity on plain radiographs correlate modestly with gait changes, whereas tibiotalar incongruity and length of the talar body, not flatness of the talar dome, correlate with decreased patient-reported outcome scores. Level of Evidence: Level III, prognostic.